Sound-Based Light Control System in The Ship's Room With Uno Arduino - Kurniawan, Edi; Adnin Nanda Pratama, Maverik; Eddi, Eddi (SAINSTECH NUSANTARA, 2024)
Technological advances have given us many advantages, electronic devices and new procedures. Technological advances can also have negative side impacts if not used appropriately and correctly. In particular, it covers risks arising from careless use of electricity and accidents in the workplace. The research method used is research and development; data is obtained by carrying out direct observations on the tools when assembled. With this sound-based system for turning on the lights, you will be able to control the turning on and off of the lights just by sound, which means you can find out whether the lights are on or off and will be given information via a 16x2 LCD which has been programmed on the Arduino UNO to detect frequencies. The sound sensor on the system receives sound.